A response to the Covid-19 crisis for the Arts in Ireland and Impact of the Coronavirus on the Northern Ireland Arts Sector - O'Brien, Maria; Costelloe, Lucy (Irish Journal of Arts Management and Cultural Policy, 2021)
Focusing on two policy reports addressing the crisis in the arts arising from COVID-19, this paper interrogates the policy responses to the challenges for the arts sector in Ireland and Northern Ireland. The enduring challenges of precarity in the arts and the problem of the digital divide are reinforced by the challenges of COVID-19.